Triptolide inhibits oxidative stress and inflammation via the microRNA-155-5p/brain-derived neurotrophic factor to reduce podocyte injury in mice with diabetic nephropathy. Issue 5 (2nd May 2022) - Gao, Jian; Liang, Zheng; Zhao, Fei; Liu, Xiaojing; Ma, Ning
ABSTRACT: Diabetic nephropathy (DN) is a complication of diabetes. This study sought to explore the mechanism of triptolide (TP) in podocyte injury in DN. DN mice were induced by high-fat diet&streptozocin and treated with TP. Fasting blood glucose, 24 h urine microalbumin (UMA), the pathological changes of renal tissues, and ultrastructure of renal podocytes were observed. Podocytes (MPC5) were induced by high-glucose (HG) in vitro and treated with TP or microRNA (miR)-155-5p mimics, with Irbesartan as positive control. Reactive oxygen species (ROS) and levels of oxidative stress (OS) and inflammatory factors in MPC5 were detected. The levels of miR-155-5p, podocyte marker protein Nephrin, and inflammatory factors in mice and MPC5 were detected. The targeting relationship between miR-155-5p and brain-derived neurotrophic factor (BDNF) was verified. The expression levels of BDNF were detected. miR-155-5p mimics and overexpressed (oe)-BDNF plasmids were co-transfected into mouse podocytes treated with HG and TP. TP reduced fasting glucose and 24 h UMA of DN mice, alleviated the pathological damage and podocyte injury, up-regulated Nephrin level, and down-regulated miR-155-5p. TP down-regulated the high expression of miR-155-5p in HG-induced MPC5 cells and inhibited HG-induced OS and inflammatory injury, and the improvement effect of TP was better than Irbesartan. Overexpression of miR-155-5p reversed the protective effect of TP on injured mouse podocytes. miR-155-5p targeted BDNF. oe-BDNF reversed the inhibitory effect of oe-miR-155-5p on TP protection on podocyte injury in mice. Overall, TP up-regulated BDNF by inhibiting miR-155-5p, thus inhibiting OS and inflammatory damage and alleviating podocyte injury in DN mice. Graphical abstract: uf0001